2023
DOI: 10.3390/cells12081111
|View full text |Cite
|
Sign up to set email alerts
|

Partial Inhibition of Complex I Restores Mitochondrial Morphology and Mitochondria-ER Communication in Hippocampus of APP/PS1 Mice

Abstract: Alzheimer’s disease (AD) has no cure. Earlier, we showed that partial inhibition of mitochondrial complex I (MCI) with the small molecule CP2 induces an adaptive stress response, activating multiple neuroprotective mechanisms. Chronic treatment reduced inflammation, Aβ and pTau accumulation, improved synaptic and mitochondrial functions, and blocked neurodegeneration in symptomatic APP/PS1 mice, a translational model of AD. Here, using serial block-face scanning electron microscopy (SBFSEM) and three-dimension… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 101 publications
1
5
0
Order By: Relevance
“…Interestingly, as is the case of complex I inhibitor metformin or complex I, III and V inhibitor resveratrol, continuous application of these compounds is safe 39,59 . Consistent with our previous findings in AD mice [37][38][39][40][41]43 , 3-day CP2 treatment in Ndufs4 -/males and females enhanced mitochondrial biogenesis, evident by increased mitochondrial translation and activation of transcription factors Tfeb and Tfam, which lead to the augmented expression of genes involved in the OXPHOS, the TCA cycle, and the mitochondria specific neuroprotective deacetylase Sirtuin 3 60 . Concomitantly increased mitochondrial biogenesis, translation and mitophagy indicate augmented mitochondrial turnover and replenishment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Interestingly, as is the case of complex I inhibitor metformin or complex I, III and V inhibitor resveratrol, continuous application of these compounds is safe 39,59 . Consistent with our previous findings in AD mice [37][38][39][40][41]43 , 3-day CP2 treatment in Ndufs4 -/males and females enhanced mitochondrial biogenesis, evident by increased mitochondrial translation and activation of transcription factors Tfeb and Tfam, which lead to the augmented expression of genes involved in the OXPHOS, the TCA cycle, and the mitochondria specific neuroprotective deacetylase Sirtuin 3 60 . Concomitantly increased mitochondrial biogenesis, translation and mitophagy indicate augmented mitochondrial turnover and replenishment.…”
Section: Discussionsupporting
confidence: 92%
“…The detailed investigation of the impact of Ndufs4 knockout on the assembly and stability of complex I revealed that other subunits or OXPHOS complexes, including Ndufaf2 and complex III, could function as stabilizing factors to explain a residual activity of complex I (~26% in isolated mitochondria) in the Ndufs4 -/mouse brain 30,54 . Extensive studies conducted to understand the mechanism of CP2 suggest that binding and mild inhibition of complex I is required to alter AMP/ATP ratio, activate AMPK and the subsequent signaling cascade [37][38][39][40][41]43 . Our studies in aging WT or symptomatic AD mice suggest that mild inhibition of complex I could be beneficial despite a presence of mitochondria with altered dynamics and function, similar to data generated with metformin 59,63 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such a mitochondrial phenotype was later observed in the brains of OXYS rats, a model of sporadic AD [ 93 ], and in aged non-human primates [ 94 ]. Very recently, Panes and colleagues [ 95 ] reported that the MOAS morphology represented approximately 80% of the total mitochondria in the hippocampi of APP/PS1 mice. Moreover, they observed a significant interaction between MOAS and endoplasmic reticulum (ER) membranes, forming extensive mitochondria–ER contact sites (MERCS).…”
Section: Mitochondria (Dys)function In Alzheimer’s Disease: a Brief O...mentioning
confidence: 99%
“…Moreover, they observed a significant interaction between MOAS and endoplasmic reticulum (ER) membranes, forming extensive mitochondria–ER contact sites (MERCS). Although the exact role of such an interaction remains unclear, the authors showed that reestablishing energy homeostasis reduced MOAS formation, MERCS coverage, and ER stress and enhanced the mitochondrial dynamics [ 95 ]. Alongside alterations in the CNS, previous studies refer to the existence of an abnormal mitochondrial distribution and morphology in fibroblasts from sporadic AD cases due to a reduction in Drp1 protein levels [ 96 ].…”
Section: Mitochondria (Dys)function In Alzheimer’s Disease: a Brief O...mentioning
confidence: 99%